Work, Human Agency and Organizational Forms: An Anatomy of Fragmentation - Kallinikos, Jannis (Organization studies, 2003)
This article is concerned with the changing premises of human involvement in organizations underlying current employment and labour trends. The appreciation of these trends is placed in the wider historical context signified by the advent of modernity and the diffusion of the bureaucratic form of organization. The article attempts to dissociate bureaucracy from the dominant connotations of centralized and rigid organizational arrangements. It identifies the distinctive mark of the modern workplace with the crucial fact that it admits human involvement in non-inclusive terms. Modern humans are involved in organizations qua roles, rather than qua persons. Innocent as it may seem, the separation of the role from the person has been instrumental to the construction of modern forms of human agency. An organizational anthropology is thereafter outlined based on Gellner's conception of `Modular Man'. Modernity and bureaucracy construe human beings as assemblages of relatively independent behavioural modules that can be invoked individually or in combination to respond to the differentiated character of the contemporary world. While the occupational mobility and organizational flexibility currently under way presuppose a model of human agency that recounts basic attributes of the modular human, they at the same time challenge it in some important respects.